PorV is an Outer Membrane Shuttle Protein for the Type IX Secretion System - Michelle D. Glew (Nature Portfolio, 2017)
Abstract Porphyromonas gingivalis is a keystone pathogen associated with chronic periodontitis. Major virulence factors named gingipains (cysteine proteinases, RgpA, RgpB and Kgp) are secreted via the Type IX Secretion System (T9SS). These, together with approximately 30 other proteins, are secreted to the cell surface and anchored to the outer membrane by covalent modification to anionic lipopolysaccharide (A-LPS) via the novel Gram negative sortase, PorU. PorU is localised on the cell surface and cleaves the C-terminal domain signal (CTD) of T9SS substrates and conjugates their new C-termini to A-LPS. A 440 kDa-attachment complex was identified in the wild-type (WT) comprising of PorU:PorV:PorQ:PorZ. In mutant strains, sub-complexes comprising PorU:PorV or PorQ:PorZ were also identified at smaller native sizes suggesting that PorU and PorZ are anchored to the cell surface via interaction with the PorV and PorQ outer membrane proteins, respectively. Analysis of porU mutants and a CTD cleavage mutant revealed accumulation of immature T9SS substrates in a PorV-bound form. Quantitative label-free proteomics of WT whole cell lysates estimated that the proportion of secretion channels:attachment complexes:free PorV:T9SS substrates was 1:6:110:2000 supporting a role for PorV as a shuttle protein delivering secreted proteins to the attachment complex for CTD signal cleavage and A-LPS modification.